2015
DOI: 10.1177/0394632015575950
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and histopathological alterations induced by cypermethrin in rat kidney and liver: Protection by sesame oil

Abstract: Pesticides are widespread synthesized substances used for public health protection and agricultural programs. However, they cause environmental pollution and health hazards. This study aimed to examine the protective effects of sesame oil (SO) on the genetic alterations induced by cypermethrin (CYP) in the liver and kidney of Wistar rats. Male rats were divided into four groups, each containing 10 rats: the control group received vehicle, SO group (5 mL/kg b.w), CYP group (12 mg/kg b.w), and protective group r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 29 publications
6
23
0
Order By: Relevance
“…This is consistent with the results of Solimon et al. [48] where CYP induced the expression of the proinflammatory cytokines IL-6 and TNF- α in rats. The increase observed in IL-6 and TNF-α levels in CYP-exposed rats thus implies the induction of inflammation by CYP exposure.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is consistent with the results of Solimon et al. [48] where CYP induced the expression of the proinflammatory cytokines IL-6 and TNF- α in rats. The increase observed in IL-6 and TNF-α levels in CYP-exposed rats thus implies the induction of inflammation by CYP exposure.…”
Section: Discussionsupporting
confidence: 93%
“…Elevated AOPP concentrations in the organs are also a pointer to the degree of damage done by CYP on the tissue protein components. These results further confirmed earlier reports implying the ability of CYP to cause increased ROS generation and oxidative damage in liver and kidney of rat [47, 48]. Bhushan et al.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Sesame oil was shown to exert protective effects against cypermethrin-induced damage in genomic DNA and histopathological changes in the brain or hematotoxicities [13,43]. It was reported to prevent the deleterious effect of cypermethrin in rat liver and kidney [44,45]. The present observations showed that the SSM-mediated inhibition of I Na could be counteracted by a further application of tefluthrin, structurally similar to cypermethrin, suggesting that pyrethroid-induced neurotoxicity could be reversed by SSM or SesA.…”
Section: Discussionmentioning
confidence: 49%
“…Our findings revealed that subacute intoxication of rats with bifenthrin caused significant elevations in serum BUN and creatinine levels. The nephrotoxic effects of other pyrethroids including cypermethrin and deltamethrin were previously reported (Gündüz et al, 2015;Soliman et al, 2015). BUN is produced from ammonia in liver and excreted by glomerular filtration.…”
mentioning
confidence: 78%